Challenge for public and private sector in implementation IAS-IFRS IPSAS in Colombia and specially in the property plant and equipment (2015)
Inside of normal change that it’s present in the society, product it self of evolution, it’s present the modernization, for Colombia, in this moment the actualization is focused in the financial area and for it’s that the business of sector public and private should adopt and to implement the international accounting rules and international information accounting rules, being that in this universal lenguage is speak in the a lot of countries, for it is as this country can continue being competitive it corresponds its aplication and to use constant and imperative, with special emphasis on one of the most significant such as property, plant and equipment items.